2013
DOI: 10.7860/jcdr/2013/6035.3331
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome in Turkmen Ethnic Groups in Gorgan

Abstract: Introduction: It has been estimated that the metabolic syndrome may predict cardiovascular disease and the occurrence of sudden death, independent of the presence of other cardiovascular risk factors. The aim of the present study was to assess the metabolic syndrome among Turkmen women in this area. Material and Methods:The present study consisted of 160 Turkmen women. Baseline data and prevalence of metabolic syndrome and the components of metabolic syndrome in Turkmen women were determined. Observations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Low levels of HDL are associated with risk factors for metabolic syndrome. Shahini, Shahini, and Marjani (2013) demonstrated that the prevalence of low HDL cholesterol in a Turkmen population suffering metabolic syndrome was 78.57%.…”
Section: Discussionmentioning
confidence: 98%
“…Low levels of HDL are associated with risk factors for metabolic syndrome. Shahini, Shahini, and Marjani (2013) demonstrated that the prevalence of low HDL cholesterol in a Turkmen population suffering metabolic syndrome was 78.57%.…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of metabolic syndrome is influenced by dissimilarities in genetic factors, age, gender, diet and physical activity [2]. Studies of Marjani et al indicated that metabolic syndrome is changed in different ethnic and age groups, different diseases and postmenopausal women [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Progranulin is known with different names such as granulin-epithelin precursor [17], proepithelin [18][19] and acrogranin [20].…”
Section: Introductionmentioning
confidence: 99%
“…Some other studies in Turkey, India, Iran, African Americans, Mexican Americans have shown that women to be much more frequently affected [3,9], while in France and Australia the metabolic syndrome was found to be more common among men [3]. In Fars and Sistanee ethnic group in Gorgan (Iran), the frequency of metabolic syndrome was 20.62% and 23.75%, respectively [56][57].…”
Section: Different Viewsmentioning
confidence: 93%